2016
DOI: 10.1007/s11999-016-4759-6
|View full text |Cite
|
Sign up to set email alerts
|

Hard-on-Hard Bearings Are Associated With Increased Noise Generation in Young Patients Undergoing Hip Arthroplasty

Abstract: Background Patient-perceived noise from prostheses after total hip arthroplasty (THA) does occur, yet questions remain including the overall frequency of this finding, demographic and prosthesis-related factors, and the association of noise generation with patient-reported outcomes. Questions/purposes The purposes of this study were (1) to determine the frequency with which patients report noise coming from the hip after THA; (2) to identify patient and prosthesis-related factors associated with noise generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…However, in a recent study, noise was found to be associated with pain (Nam et al. 2016). The cause of noise from THAs may be multifactorial, but an association between higher inclination angle and squeaking was found in MoM THAs (Bernasek et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a recent study, noise was found to be associated with pain (Nam et al. 2016). The cause of noise from THAs may be multifactorial, but an association between higher inclination angle and squeaking was found in MoM THAs (Bernasek et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, concerns over noise, squeaking, micro-separation, increased susceptibility in component-to-component impingement and fracture risk still remain controversial. Despite these controversies, more careful monitoring is warranted when using COC articulation in larger heads, because some studies have suggested that stiff ceramic heads may increase stress over the trunnion compared to metallic heads 47) .…”
Section: Ceramic On Ceramic (Coc) As An Articulating Surfacementioning
confidence: 99%
“…However, concerns of CoC bearing surface's negative property remained 18 19) . Besides problems of squeaking and fracture of ceramic head, some paper reported possibility of increasing stress on trunnion compared with metallic head when using big size of femoral head 20) .…”
Section: Discussionmentioning
confidence: 99%